The new revolution in toxicology: The good, the bad, and the ugly. (11th March 2013) - Davis, Myrtle; Boekelheide, Kim; Boverhof, Darrell R.; Eichenbaum, Gary; Hartung, Thomas; Holsapple, Michael P.; Jones, Thomas W.; Richard, Ann M.; Watkins, Paul B.
Abstract : In 2007, the United States National Academy of Sciences issued a report entitled Toxicity Testing in the 21 st Century: A Vision and a Strategy . The report reviewed the state of the science and outlined a strategy for the future of toxicity testing. One of the more significant components of the vision established by the report was an emphasis on toxicity testing in human rather than animal systems. In the context of drug development, it is critical that the tools used to accomplish this strategy are maximally capable of evaluating human risk. Since 2007, many advances toward implementation of this vision have been achieved, particularly with regard to safety assessment of new chemical entities intended for pharmaceutical use.